ANALISIS PERTUMBUHAN EKONOMI DAN DISTRIBUSI PENDAPATAN DI PROVINSI SULAWESI TENGGARA - Muhammad Taufiq Hadi; Zaenuddin Saenong; Muhammad Nur Afiat (JEP (Jurnal Ekonomi Pembangunan), 2019)
The research was conducted to discover the core sectors that have contributed the most to economic growth, by analyzing the development of economic structures and the growth rate of the PDRB in the excellent sectors, as well as to know the distribution of income in southeastern Sulawesi province in 2014-2018. This research uses the Deductive-quantitative method. This type of research data uses secondary data. There are two variables studied in this research, i.e. (1) Economic growth and (2) income distribution. The data collection techniques used in this study are documentation methods and library studies. The primary data used are secondary data based on time series. The data collected are analyzed using descriptive techniques and calculation techniques from the LQ, Shift Share and Williamson indices. The results showed that the development of the PDRB structure in southeastern Sulawesi province dominates 7 basic sectors, where mining and excavation sectors contribute the most, and subsequently in a sequence the agriculture, Forestry and Fisheries, Construction, Transportation and Storage, Education Services, Public Administration, Defense, and Mandatory Social Security Sectors, and water supply, waste management, waste management and recycling.